The establishment of institutional repository : a brief comparative study between the national university of malaysia and the university of liverpool - Sidek, Harith Faruqi; Ishak, Azmah; Mohd Saleh, Noor Farhana; Zainol, Zanariah (Persatuan Pustakawan Malaysia, 2011)
The implementation of an institutional repository has never been an easy task since there are challenges that need to be addressed in the pre-implementation process. There are various factors that can interfere with the smooth development of the IR. Awareness, budgeting, technology and human factors such as staffing and depositors’ behaviour all become part of the challenges. Even with thorough planning, there is no guarantee that the IR will work smoothly as there are various post-implementation issues awaiting. As a result, institutions must provide solution plans to overcome all these challenges. This article is a brief comparative study on the challenges and issues experienced by the National University of Malaysia and the University of Liverpool on the establishment of an IR. The discussions are centered on issues such as depositors’ behavior, management, access and sustainability.